Theory of mind and coming-out milestones: a study of sexual and gender minority adolescents in Germany - Osterhaus, Christopher; Ioverno, Salvatore (Universität Vechta, 2025)
The coming-out process is a significant aspect of identity formation for sexual and gender minority (SGM) youth, often shaped by complex interpersonal and societal factors. This study investigates the role of theory of mind (ToM) – the ability to understand others’ mental states – in predicting key coming-out milestones among SGM adolescents. A sample of 148 teenagers (ages 13–19) in Germany, who were mostly assigned female at birth (AFAB), completed an online survey assessing ToM, self-esteem, internalized sexual stigma, concealment, bullying experiences, and the timing of self-identification and disclosure. Higher ToM abilities were associated with earlier public disclosure and a shorter gap between self-identification and the first coming out, although not with earlier self-identification. ToM was unrelated to active concealment behaviors but correlated negatively with internalized sexual stigma. Participants who had not yet come out reported longer concealment durations when anticipating negative reactions from peers. These findings suggest that ToM may support SGM youth in navigating disclosure decisions, particularly among AFAB adolescents. Self-identification, in turn, may rely more on introspective processes. The study highlights the importance of social-cognitive skills in identity-related transitions and underscores the need for future research to explore these mechanisms across more diverse gender groups and cultural contexts.
Keywords: Sexual and gender minority (SGM) youth; Theory of mind (ToM); Coming out; Self-recognition; Concealment; Philosophie und Psychologie::150 Psychologie::150 Psychologie